FAKTOR PENYEBAB KECANDUAN JUDI ONLINE DI KALANGANREMAJA SEBAGAI DAMPAK DARI WIFI HOTSPOTDI DESA KAUMAN, KEMUSU, BOYOLALI - KHOMPRIY, MUH. ANTOK NUR; , Dra. Hj. Sri Gunarsih, SH., MH (2017)
This study aims to: (1) to describe the behavior of adolescents in Kauman Kemusu Boyolali District of the online gambling addiction; (2) determine the factors that cause adolescents in Kauman Kemusu Boyolali District of becoming addicted to online gambling; (3) determine the supply area Hotspot (WiFi) has become one of the causes of teenagers in Kauman Kemusu Boyolali District of online gambling addiction. This research includes qualitative research conducted in the field. Sources of data obtained through informants, places and events, as well as documents. This research use descriptive method. The technique of collecting data using interviews and observation. Interviews were conducted with visitors / pilgrims, cemetery caretaker, and kiai (religious teachers) or scholars of Islamic religious leaders. Data were analyzed using qualitative analysis. The procedures in this study, there are four stages: pre-field, fieldwork, data analysis and documentation analysis. The results showed that: (1) The behavior of teenagers in Kauman District of Kemusu Boyolali addicted to online gambling shows characteristics as follows: spend more time playing online gambling, physical activity decline and neglect, avoid activities important life, decrease socialization process, it is difficult to decide desire to gamble online, as well as ignoring the work and personal obligations; (2) factors that cause adolescents in Kauman District of Kemusu Boyolali become addicted to online gambling, among others: less attention than the nearest person, stress or depression, lack of control, lack of activity, environmental and social, as well as the parents' parenting is not quite right ; (3) Provision of area Hotspot (WiFi) in Kauman Subdistrict Boyolali Kemusu not a factor that causes teens addicted to online gambling. Provision area Hotspot (WiFi) in Kauman Kemusu District of Boyolali has been used positively by local people to access information and data communications.